1990
DOI: 10.1212/wnl.40.4.626
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of clinically diagnosed Alzheimer's disease and other dementing disorders

Abstract: The purpose of this study was to investigate the prevalence of dementia in an Italian population using a door-to-door 2-phase design. As part of a social and health survey, we administered the Hodkinson abbreviated mental test to all persons over age 59 residing in the Commune of Appignano on January 1, 1987 (N = 778). We then investigated all subjects scoring 7 or less on the cognitive test following a standardized diagnostic protocol. We found 48 patients affected by dementia, yielding a crude prevalence rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
118
5
7

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(156 citation statements)
references
References 0 publications
26
118
5
7
Order By: Relevance
“…There are other studies which showed a similar trend, wherein a higher prevalence of dementia was seen in less educated populations (18)(19)(20).…”
Section: Discussionsupporting
confidence: 60%
“…There are other studies which showed a similar trend, wherein a higher prevalence of dementia was seen in less educated populations (18)(19)(20).…”
Section: Discussionsupporting
confidence: 60%
“…Premorbid IQ and vocabulary have proven to be strong proxies for CR, in that they are associated with slower rates of cognitive decline in normal aging and reduced risk of developing dementia (e.g., S. M. Albert & Teresi, 1999;Alexander et al, 1997;Corral, Rodríguez, Amenedo, Sánchez, & Díaz, 2006; Solé-Padullés et al, 2007). Similarly, education has been shown to impart reserve over an individual's lifetime (Evans et al, 1993;Mortel, Meyer, Herod, & Thornby, 1995; Rocca et al, 1990;Stern et al, 1994), and individuals with higher levels of education demonstrate slower cognitive and functional decline during normal aging (M. S. Albert et al, 1995;Butler, Ashford, & Snowdon, 1996;Chodosh, Reuben, Albert, & Seeman, 2002;Christensen et al, 1997;Colsher & Wallace, 1991;Farmer, Kittner, Rae, Bartko, & Regier, 1995;Lyketsos, Chen, & Anthony, 1999;Snowdon, Ostwald, & Kane, 1989). Moreover, we have successfully used IQ, vocabulary, and education as proxies for CR in previous behavioral and neuroimaging studies (e.g., Habeck et al, 2005;Scarmeas et al, 2004;Stern et al, 2005Stern et al, , 2008.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Regional demographics also will affect the percentage of Alzheimer's cases found in each state. Indeed there appears to be a higher prevalence in rural areas [6] and among those with less education [7,8]. It is this particular subset of DAT patients that often results in search and rescue incidents.…”
Section: Introductionmentioning
confidence: 99%